Strategy of scientific degree for the University of Medical Sciences in Santiago de Cuba - Liuba González Espangler; Melba Alina Borges Toirac; Sara Riccis Salas Palacios; Migdalia Fernández Villalón; Nadina Travieso Ramos (Centro Provincial de Información de Ciencias Médicas, 2022)
The strategies for the training of Doctors in Science in the higher education institutions, is a guarranty to increase quality  in the training of professionals through the integration of sustantive processes. Taking into account these referents, a proposal of perfectioning the scientific degree institutional estrategy is presented  for the Medical Sciences University in Santiago de Cuba in the period from 2022 to 2024, which has a systemic character, and includes in its structure four components: background, characterization of the Medical Sciences University in Santiago de Cuba  (MSU-SC), strategic planning (mision, vision, objective and strategic actions), and evaluation. Its implementation, as a group of sequential and interrrelated actions, will allow to achieve a significant  impact  in the increase of  scientific results and in the external recognition and visibility of this Center of higher studies.